2004
DOI: 10.14507/epaa.v12n49.2004
|View full text |Cite
|
Sign up to set email alerts
|

Age & Achievement

Abstract: There is continuing controversy about the optimal or appropriate age at which children should start school. The purpose of this study is to examine the relationship between age and achievement. It is an attempt to evaluate the hypothesis that older students fare better academically than their younger classmates. Findings indicate that on average for students in elementary school there is positive linear relationship between age and achievement for age normal peers. Even though there is positive linear relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 17 publications
1
17
0
2
Order By: Relevance
“…Many studies, however, found that the academic achievement advantage was small, most pronounced in the first years, and declined sharply in subsequent years. Of particular interest to this study, two of the reviewed studies, Grissom (2004) andMartin (2009), suggested that age differences between peers falling within the normal 12 month range caused by variations in students' birth month, may have different effects on achievement than age differences due to delayed school entry.…”
Section: -Summarymentioning
confidence: 97%
See 4 more Smart Citations
“…Many studies, however, found that the academic achievement advantage was small, most pronounced in the first years, and declined sharply in subsequent years. Of particular interest to this study, two of the reviewed studies, Grissom (2004) andMartin (2009), suggested that age differences between peers falling within the normal 12 month range caused by variations in students' birth month, may have different effects on achievement than age differences due to delayed school entry.…”
Section: -Summarymentioning
confidence: 97%
“…Age-normal students: Students who did not delay school entry, i.e., enrolled in school when they were age-eligible (Grissom, 2004).…”
Section: School-entry Age (Sea)mentioning
confidence: 99%
See 3 more Smart Citations